Regional Acceleratory Phenomenon after Orthodontic Force Exertion in Ovariectomized Rats - TSOLAKIS, A. I.; KHALDI, L.; BITSANIS, I.; DONTAS, I. A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The application of orthodontic forces may be one of the factors that produce a regional acceleratory phenomenon (RAP) in mandibular and maxillary bones. The effect of exerted forces on bone tissue ahead of their point of application has not been extensively studied. Moreover, limited information exists regarding this phenomenon on osteoporotic bone. The study aim was to examine the role of orthodontic forces on the expression of RAP in normal and osteoporotic mature rats. Thirty-six eight-month-old skeletally mature female Wistar rats, half of which had been previously ovariectomized (OVX) at the age of 6 months, were subjected to orthodontic movement of the upper right first molar. An orthodontic force of 60 gr* was generated through a closed coil spring for 14 days. The maxillae were then removed and the area ahead of the first molar was examined histologically. On the side of orthodontic force application, distortion of bone structure and woven bone formation were observed in non-OVX rats, whereas in the OVX rats, extensive remodeling was apparent. In conclusion, the application of orthodontic forces on both normal and osteoporotic mature rats in the present study created a RAP ahead of the loaded teeth demonstrated histologically, indicating increased bone resorption and formation in the OVX rats.